Réception d’une loi scolaire par les instances locales. L’exemple des écoles primaires supérieures (1833-1850) - Angélique Blanc-Serra (Recherches en Éducation)
The structure and adoption of a new school system — the Senior Primary School promulgated by the law of 28 June 1822 – provide us a perspective on the thinking of local authorities, especially concerning education policy. Once having recalled the historical context of the Guizot law and its contents, the article focuses next on different local approaches to applying the law. These reflect a variety of objectives and practices that were closely linked to local economic priorities or other specific needs. These various approaches furthermore allow us to observe tensions between national intentions and rooted local interests that challenged the appropriation of this educational law. The results of this study nonetheless suggest that the reception of the law – however vague the law's guidelines on Senior Primary Schools – contributed positively at the local level.